From School to Work: Contemporary TVET Regional Experiences : Final Report of the Seminar 23 - 30 January 2007 - (:unkn) unknown (National Institute for Educational Policy Research, 2007)
"The meeting focussed primarily on Technical and Vocational Education and Training (TVET) as a means to preparing school leavers for the world of work and on policies and strategies supporting young people through the actual transition process. In line with mandates of NIER and UNESCO-UNEVOC to provide platforms for an international exchange of information and good practice, the seminar served to increase the understanding of contemporary regional experiences of transition to work issues in the Asia-Pacific region. Several country case studies on school-to-work transition were presented, different approaches and strategies were discussed, and common concerns and issues related to school- to-work transition were identified during the seminar. Based on these key issues and as an outcome of intensive group work, the participants formulated a set of recommendations for a regional strategy on the improvement of TVET." (Autorenreferat; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; I 2.3.5 Australien, Ozeanien; I 2.3.4 Asien; Berufsausbildung; Berufseinmündung; Erste Schwelle; Australien; Bangladesch; Kambodscha; China; Fidschi; Indonesien; Japan; Laos; Malaysia; Mongolei; Nepal; Südkorea; Sri Lanka; Thailand; Vietnam